Studi Kekuatan Pasangan Batu Bata Pasca Pembakaran Menggunakan Bahan Additive Zeolit - Fernanda, Aldy; Iswan, Iswan; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
In this research the reseacher used the worst material of soil with additive materials named theash of bagasse in purpose to utilize the waste and to increase the strength of the bricks so that itcan produce cheap bricks with good quality that can be an alternative for bricks industries.Soil samples were tested in this study is derived from the silt soil region Nyunyai road,Kec.Rajabasa. Variations in the levels of the mixture used is 6%, 8%, 10%, and 12% and dryingfor 7 days, with burning treatment and without burning treatment. Based on the results of physicalexamination native land, USCS classify soil samples as fine-grained soil and belong to the CLgroup.The results showed that the brick-making post-combustion using zeolite mixture meets theIndonesian National Standard (SNI) bricks for building materials. In general, the addition ofzeolite material in the soil reduces the value of the density of the soil mixture. For the compressivestrength of bricks without combustion and combustion processes are best shown in the addition ofa mixture of 10%-12%.Keywords: Bricks, silt soil, zeolite, compressive strength